The demographic transformations of citizenship / Heli Askola. - Askola, Heli (Cambridge studies in law and society., 2016)
The Demographic Transformations of Citizenship examines how attempts by contemporary states to govern demographic anxieties are shaping ideas about citizenship both as a boundary-maintaining mechanism and as an ideal of equal membership. These anxieties, while most often centred upon immigration, also stem from other demographic changes unfolding in contemporary states - most notably, the long-standing trend towards lower birth rates and consequent population ageing. With attention to such topics as control over borders, national identity, gender roles, family life and changing stages of life, Askola examines the impact of demographic changes, including but not limited to immigration. Drawing from a variety of disciplines, including law, demography, and sociology, this book discusses how efforts to manage demographic anxieties are profoundly altering ideas about citizenship and belonging.